Energy communities in heritage districts: Energy Community (EC) Alhambra Districts (Grenade) - Pérez-Pérez, Belén (Revista de Estudios Andaluces, 2023)
Energy communities in Spain have legal difficulties for their implementation, which are multiplied in protected areas due to its cultural heritage. The aim of this work is to study the strategies to constitute an urban energy community in two heritage districts in the city of Granada (Spain) as well as the usefulness for its neighbours, being part of it. This study uses a methodology based on a literature and documentary review, the accompaniment of the community and the mapping of options, in conjunction with a survey of the neighbouring districts and its analysis. The results show the utility in sharing energy collectively and exploring alternatives for integration into the cultural heritage. This interest transcends the economic sphere and focuses on improving the environmental and social sustainability of their districts. In conclusion, it is found that, despite the existence of various projects for the integration of photovoltaic solar energy into the cultural heritage, there is still no effective solution.